Psychodynamic model of career decisions of selected retireable faculty implications to career counseling - Montano, Julian III (Philippine Journal of Counseling Psychology, 2005)
This research adopted the psychodynamic model to draw the map in career decisions that are reflected in the spontaneity, compulsion, precision and expressiveness of career choices. Specifically, it explored the career decisions of retiring faculty (n=2) in a university in Southern Manila by analyzing the "pakikipagkwentuhan" as specific source of gathering data through an interview session. Implications for career counseling, faculty career development and issues on retirement are discussed.